Benefical effects of palmvitee on aortic oxidative stress in hyperhomocysteinemics rats - Ku Zaifah, Norsidah; Yusuf, Kamisah; Yusuf, Ahmad Asmadi; Ayob, Azizi (2009)
Hyperhomocysteinemia which can be induced by dietary high methionine has been reported to increase oxidative stress in cardiovascular organs. The aims of the study were to investigate the effects of palmvitee on aortic oxidative stress induced by high methionine diet in rats, and to compare it with folate, the current treatment for hyperhomocysteinemia. Male Wistar rats were divided into six groups. The first group was given normal rat chow (control), while the second group was fed a high methionine (1%) diet for ten weeks. The other four groups were given a high methionine diet throughout the ten-week study, into which folate (8 mg/kg diet) or palmvitee at doses of 30, 60 and 150 mg/kg diet was added from week 6 to week 10. At the end of the study period, the rats were sacrificed. Plasma homocysteine level was elevated after 5 and 10 weeks of dietary high methionine. Supplementations with folate and 150 mg/kg diet palmvitee had prevented the elevation. Moreover, folate and all palmvitee-supplemented groups had a significantly lower aortic lipid peroxidation (TBARS) content than the methionine alone group. Dietary high methionine also reduced plasma nitric oxide, which reduction was prevented by palmvitee treatments at 60 and 150 mg/kg diet, but not by folate. In conclusion, palmvitee is slightly superior to folate in improving the aortic oxidative stress induced by high methionine diet.